2016
DOI: 10.13004/kjnt.2016.12.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Twist-Drill or Burr Hole Craniostomy for Draining Chronic Subdural Hematomas: How to Choose It for Chronic Subdural Hematoma Drainage

Abstract: ObjectiveAlthough twist-drill craniostomy (TDC) has a number of procedural advantages and an equivalent outcome compared to burr hole craniostomy (BHC) for the treatment of chronic subdural hematomas (CSDHs), the latter technique remains the preferred method. We analyzed symptomatic CSDHs in whom TDC at the pre-coronal suture entry point (PCSEP) was the primary method for hematoma drainage and BHC on the parietal was the secondary option.MethodsCSDHs in 86 consecutive patients were included. TDC at the PCSEP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Our results showed that the mean operative time (the time starts with the first surgical step and stops by its end) in our studied cases was 8.38 minutes with a mean operative room time (the time between the patient's entrance to the opera-Open Journal of Modern Neurosurgery tive theatre and his exit from it) approximately 32 minutes. Lee SJ, Hwang on 2016 in a study on twist drill evacuation of CSDH reported an operative time of 8.9 minutes which is close to our results [19].…”
Section: Primary Outcome: Operation Timesupporting
confidence: 88%
“…Our results showed that the mean operative time (the time starts with the first surgical step and stops by its end) in our studied cases was 8.38 minutes with a mean operative room time (the time between the patient's entrance to the opera-Open Journal of Modern Neurosurgery tive theatre and his exit from it) approximately 32 minutes. Lee SJ, Hwang on 2016 in a study on twist drill evacuation of CSDH reported an operative time of 8.9 minutes which is close to our results [19].…”
Section: Primary Outcome: Operation Timesupporting
confidence: 88%
“…Since both methods had similar effectiveness, the surgeon selected between TDC and BHC according to his or her own preference [18]. The TDC ensures the safety of the patient during the procedure and can be done in the treatment room on the ward under local anaesthesia [15]. These factors represent a huge advantage of this technique.…”
Section: Discussionmentioning
confidence: 99%
“…In Poland almost all patients are offered either BHC or SC. Choosing the best operation for CSDH concerned authors in the past [15, 28]. Every CSDH case differs from another, whereas systematic reviews and meta-analyses lack the individual approach to CSDH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations